Visual "literacy" : image, mind, and reality - Messaris, Paul (Westview Press, 1994)
Post-industrial humankind is inundated daily with visual images. Televisions transmit their blue haze into dark living rooms; advertisements and billboards bombard us at every turn; movies evoke tears, outrage, or hilarity; and the visual arts elicit strong emotional or intellectual responses. At almost every moment, several visual images are warring for our attention in order to make a claim, sell a product, or call us to action. Faced with visual overload, how do we interpret these images? What is happening when a picture moves us? What process takes place in our minds as we respond to such visual devices as close-ups, camera angles, and flashbacks?This book provides a foundation for answering these questions. Encouraging his readers to become “visually literate,” Paul Messaris takes them on a journey through four major conceptual levels of understanding: imparting visual literacy as a prerequisite for comprehending visual media; creating awareness of the general cognitive consequences of visual literacy; making us alert to visual manipulation; and promoting aesthetic appreciation of the images we see. Taken together, these approaches provide a comprehensive view of how visual images are produced and interpreted, and of what their potential social consequences may be.